The prevalence of Middle East respiratory syndrome coronavirus (MERS‐CoV) antibodies in dromedary camels in Israel. (31st May 2018) - Harcourt, Jennifer L.; Rudoler, Nir; Tamin, Azaibi; Leshem, Eyal; Rasis, Michal; Giladi, Michael; Haynes, Lia M.
Abstract: Middle East respiratory syndrome coronavirus, MERS‐CoV, was identified in Saudi Arabia in 2012, and as of January 29, 2018, there were 2, 123 laboratory‐confirmed MERS‐CoV cases reported to WHO (WHO, 2018, https://www.who.int/emergencies/mers-cov/en/ ). Multiple studies suggest that dromedary camels are a source for human MERS‐CoV infection. MERS‐CoV‐specific antibodies have been detected in the serum of dromedary camels across Northern Africa and across the Arabian Peninsula. Israel's geographic location places Israel at risk for MERS‐CoV infection. To date, MERS‐CoV‐related illness has not been reported and the burden of MERS‐CoV infection in the Israeli population is unknown. The seroprevalence of MERS‐CoV‐specific antibodies in Israeli dromedary camels is unknown. The objective of this study was to determine the prevalence of MERS‐CoV seropositivity in dromedary camels in Israel. The prevalence of MERS‐CoV antibodies in Israeli camels was examined in 71 camel sera collected from four farms across Israel by MERS‐CoV‐specific microneutralization (Mnt) assay and confirmed by MERS‐CoV‐specific immunofluorescence assay (IFA). Although this study cannot rule out potential antibody cross‐reactivity by IFA, the presence of bovine coronavirus‐specific antibodies do not appear to impact detection of MERS‐CoV antibodies by Mnt. MERS‐CoV neutralizing antibodies were detectable in 51 (71.8%) camel sera, and no association was observed between the presence of neutralizing antibodies and camel age or gender. These findings extend the known range of MERS‐CoV circulation in Middle Eastern camels. The high rate of MERS‐CoV‐specific antibody seropositivity in dromedary camels in the absence of any reported human MERS cases suggests that there is still much to be learned about the dynamics of camel‐to‐human transmission of MERS‐CoV.